Layers of learning : using read-alouds to connect literacy and caring conversations - McCarthy, JoEllen (Stenhouse Publishers, 2020)
"This book aims to help educators create a lasting literacy that goes beyond the classroom walls. Shifting the focus from literacy to literacy and life lessons, this book extends the current conversations teachers are having about growth mindset, relationships, motivation, and practices that contribute to caring classroom communities. The book is a merger of practice, theory, and children's books that focuses on connecting affective and academic standards, while also providing ideas readers can adopt or adapt immediately"--